A new piezoelectric actuator induces bone formation in vivo: a preliminary study - Reis, J (2013)
This in vivo study presents the preliminary results of the use of a novel piezoelectric actuator for orthopedic application. The innovative use of the converse piezoelectric effect to mechanically stimulate bone was achieved with polyvinylidene fluoride actuators implanted in osteotomy cuts in sheep femur and tibia. The biological response around the osteotomies was assessed through histology and histomorphometry in nondecalcified sections and histochemistry and immunohistochemistry in decalcified sections, namely, throughMasson’s trichrome, and labeling of osteopontin, proliferating cell nuclear antigen, and tartrate-resistant acid phosphatase. After one-month implantation, total bone area and new bone area were significantly higher around actuators when compared to static controls. Bone deposition rate was also significantly higher in the mechanically stimulated areas. In these areas, osteopontin increased expression was observed. The present in vivo study suggests that piezoelectric materials and the converse piezoelectric effect may be used to effectively stimulate bone growth.